Pioneering the Road to Prosperity for the Future Workforce: Building Social Development Fund (SDF) Roadmap in Indonesia - Arie Sujito; Sugeng Bahagijo (Magister Ilmu Administrasi Publik, 2022)
The paper discusses possible solutions through the Social Development Fund (SDF) scheme to reduce and prevent educated unemployment problems. This paper uses critical discourse involving literature studies such as books, journals, reports, and online media. The findings of the research show that (1) there still a lot of educated workforces unemployed. This happens because of the mismatch between the capabilities and the goals of the industry. Technological advances invented new jobs. Therefore, it requires someone to adapt quickly, let alone the fact that (2) cooperation between ministries and the private sectors is not quite optimal. Other factors are, (3) SDF practices implementation by other countries, (4) resource availability in Indonesia to implement SDF. From this study concluded that SDF is a realistic alternative offer to be implemented in Indonesia, as an ecosystem that is able to ensure that existing sectors work optimally to establish the common goal of reducing the possibility of educated unemployment.